2001
DOI: 10.1046/j.1439-0396.2001.00315.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cellulose on the digestibility of high starch versus high fat diets in dogs

Abstract: The effects of cellulose added in three levels (7, 15 and 20% crude fibre in dry matter) to three different basal diets (a high fat diet, a high starch diet with raw starch and a high starch diet with cooked starch) on apparent digestibility were investigated in eight adult dogs. Cellulose had little effect on the apparent digestibility of fat. In the high fat diet there was no significant decrease, not even at the highest cellulose level (98.3% compared with 98.1% in the basal high fat diet). In the cooked st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 27 publications
7
28
0
1
Order By: Relevance
“…However, the amount of digestible crude protein and the quality of protein were lower in rice than in oat groats. An additive adverse effect of high fibre and starch content on faecal protein digestibility found in the study of Kienzle et al (2001) may also explain CP digestibility of barley in our experiment. Corn had the lowest crude protein content and digestibility.…”
Section: Kempe R Et Al Composition Digestibility and Nutritive Vasupporting
confidence: 55%
See 1 more Smart Citation
“…However, the amount of digestible crude protein and the quality of protein were lower in rice than in oat groats. An additive adverse effect of high fibre and starch content on faecal protein digestibility found in the study of Kienzle et al (2001) may also explain CP digestibility of barley in our experiment. Corn had the lowest crude protein content and digestibility.…”
Section: Kempe R Et Al Composition Digestibility and Nutritive Vasupporting
confidence: 55%
“…Moreover, dehulling significantly improves the nutritional quality of rice, oats and barley, which are harvested with the hulls attached, compared to other cereals, which lose their hulls during the threshing step and are handled as naked grains. The high crude fibre and cellulose contents of hulls have negative effects on the dry matter (DM), organic matter (OM), crude protein (CP), energy and mineral digestibilities of cereals in dogs (Fahey et al 1992, Lewis et al 1994, Kienzle et al 2001. The crude fibre content of oats (100-150 g kg -1 DM) is twice as high as in barley, wheat and corn, and so the apparent nutrient digestibilities of oats are, in most cases, lower than of other cereals (Moore et al 1980, Walker et al 1994.…”
Section: Kempe R Et Al Composition Digestibility and Nutritive Vamentioning
confidence: 99%
“…It is well documented that part of the fibre is fermented in the hind gut (Fahey et al, 1990b;Silvio et al, 2000) and also the negative effect of fibre on the apparent digestibility of fat, protein and available carbohydrates (Livesey, 1993;Kienzle et al, 1998aKienzle et al, , 2001Castrillo et al, 2001a).…”
Section: Empirical Equationsmentioning
confidence: 99%
“…Castrillo et al (2001b) found that when NFE was introduced as a second independent variable in addition to CF, it was negatively related to dE, (dE=101.8 -3.38 CF (%DM) -0.21 NFE (% DM); r 2 = 0.82; rsd= 1.53, CV= 1.8%), increasing explained variation by 10% given that the NFE fraction is estimated by difference, including those cell wall components that are incompletely recovered in CF residue, but are resistant to digestion in small intestine. Kienzle et al (2001) suggested different equations for the estimation of energy digestibility as a function of CF for high and low-NFE diets for dogs. When data were split into high and low-carbohydrate foods (NFE greater Castrillo et al (2001) whose set of samples averaged 446 + 9.8 g NFE/kg DM, with most of samples being over 400 g NFE/kg DM.…”
Section: Constraints Of the Nrc (2006) Approachmentioning
confidence: 99%
“…1). Considerando que os valores declarados já são limites, percebem-se, nesses casos, alimentos com qualidade comprometida, pois, além de apresentarem teor protéico insuficiente, existe uma relação inversa entre o teor de fibra e a digestibilidade da proteína da ração (Burrows et al, 1982;Kienzle et al, 2001). Em relação aos produtos standard para cães adultos, 14,3% estavam em não conformidade quanto à proteína e metade deles com mais cálcio do que foi declarado pelo fabricante.…”
Section: Resultsunclassified